City Branding and City Tourism - W. Sakti, Intan; Gaffar, Vanessa; Dewi Dirgantari, Puspo (International Journal of Psychosocial Rehabilitation, 2020)
A city can be seen from various perspectives, including tourist attraction as the ability to compete effectively in tourism with other cities. In Indonesia, cities have become tourist destinations that have undoubted advantages, although in this study the city did not have a "name reminder" as an alarm to open a description of the memory of a tourist city that had been visited, in other words, referred to as city branding. As we know, cities in Indonesia have the potential to become tourist cities, as seen from a variety of local wisdom that is owned, and it can help highlight the city. Besides, other factors that influence include accommodation and tourism services, as well as city resources such as architectural attractions, nature, and transportation availability.